(3GdeMLI aj eSGMI GdCSWMI GdeYhLgs
(3ChdgG (B:s
(3hHYO agPG JbjjO eeG JjSQ ef Yde GdeSGMI hSejJg GdeMLI ai eSGMI GdCSWMI GdeYhLI s
(3BNQgG (B:s
(3hPdc eSGMI SWMgG hgPG eG jSJQ ef eGbUOfG dg ai eSGMI GdbGYOI hGdBSWM GdeYhLI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(495 d) s
Keywords: (3GdQjGVjGJs